The RNA Directed DNA Methylation (RdDM) Pathway Regulates Anthocyanin Biosynthesis in Crabapple (Malus cv. spp.) Leaves by Methylating the McCOP1 Promoter - Yifan Xing (MDPI AG, 2021)
The synthesis of anthocyanin pigments in plants is known to be regulated by multiple mechanisms, including epigenetic regulation; however, the contribution of the RNA-directed DNA methylation (RdDM) pathway is not well understood. Here, we used bisulfite sequencing and Real Time (RT)-quantitative (q) PCR to analyze the methylation level of the promoter of constitutively photomorphogenic 1 (McCOP1) from Malus cv. spp, a gene involved in regulating anthocyanin biosynthesis. The CHH methylation level of the McCOP1 promoter was negatively correlated with McCOP1 RNA expression, and inhibiting DNA methylation caused decreased methylation of the McCOP1 promoter and asymmetric cytosine CHH methylation. We observed that the McCOP1 promoter was a direct target of the RdDM pathway argonaute RISC component 4 (McAGO4) protein, which bound to a McCOP1 promoter GGTTCGG site. Bimolecular fluorescence complementation (BIFC) analysis showed that RNA-directed DNA methylation (McRDM1) interacted with McAGO4 and another RdDM protein, domains rearranged methyltransferase 2 (McDRM2), to regulate the CHH methylation of the McCOP1 promoter. Detection of CHH methylation and COP1 gene expression in the Arabidopsis thalianaatago4, atdrm2 and atrdm1 mutants showed that RDM1 is the effector of the RdDM pathway. This was confirmed by silencing McRDM1 in crabapple leaves or apple fruit, which resulted in a decrease in McCOP1 CHH methylation and an increase in McCOP1 transcript levels, as well as in anthocyanin accumulation. In conclusion, these results show that the RdDM pathway is involved in regulating anthocyanin accumulation through CHH methylation of the McCOP1 promoter.